Strategic Implementation of AI Agents in Consulting : Use Cases and Business Benefits - Vondrášek, Viktor; Dvouletý, Ondřej; Válek, Lukáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the strategic implementation of AI agents within consulting firms, examining internal use cases, associated business benefits, challenges, and strategic approaches. Employing a qualitative methodology, seven semi-structured interviews with industry professionals were conducted in April 2025, with six held via Microsoft Teams and one in the respondent's office. The resulting data were transcribed, coded using MAXQDA, and analyzed thematically. The study found that AI agents are currently leveraged to automate repetitive tasks such as research, data handling, and document drafting, yielding substantial efficiency improvements. Significant implementation challenges include data quality and access, human factors like user adoption and skill gaps, technical limitations, and client concerns. Strategic considerations highlight diverse approaches, with hybrid models combining in-house development and outsourcing proving advantageous. Based on respondents‘ insights, the thesis concludes that effective AI agent adoption in consulting operations requires prioritizing data readiness, investing in training, managing organizational change, and maintaining client trust.
Vedoucí práce: Ondřej Dvouletý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses